AD, Volume 21, n° 4, 1996 - Full Issue - Journal System (Africa Development, 1996)
Contents Taking the Beast by its Horns: Formal Resistance to Women's Oppression in Africa Sylvia Tamale ............................... 5 L'hétérodoxie en économie politique: de l'alternative au modèle Walrassien à la synthèse avec le néo-classicisme méthodologique Hakim Ben Hammouda ......................... 23 The State, Legitimation and Human-centred Development Adebayo Ninalowo ................................55 Les communes dans le processus démocratique: la quête difficile d'un pouvoir local effectif en Mauritanie Mouhamadou Abdoul .......................... 75 Citizenship, Statehood and the Problem of Democratization in Nigeria Ehimika A. Ifidon ................................ 93 Education, caractères et développement Dénis Amoussou-Yeye ......................... 109 African Studies: A Re-assessment of Academic Tourism Since 1960 Hannington Ochwada ......................... 123 Book Review Nigeria: The Political Economy of Oil by Sarah Ahmad Khan Cyril I. Obi ........................................141 Publications Received and Acquired .......................143